Effects of nanotubes on semen quality and fertility in humans: a systematic review of literature - William Felipe Fernández Zapata; Yamile Cardona Maya; Cesar Isaza Merino; Walter D. Cardona Maya (Archivio Italiano di Urologia e Andrologia, 2024)
Background: In the medical field, it is increasingly common to observe the use of nanotubes, for example, in the administration of drugs. However, nanotubes raise concerns for male fertility due to potential effects on hormone levels and sperm quality observed in animal studies. In addition, animal exposure to multi-walled carbon nanotube models found alterations in hormone levels, sperm motility, and sperm count. Limited evidence in humans suggests no adverse effects, but further research is needed. This study aimed to perform a systematic review to assess the in vitro effects of nanotubes on semen and fertility in humans. Methods: We included all published in vitro studies about semen or sperm or male fertility and nanotubes in humans. A search was conducted in LILACS, PubMed, and SCOPUS as of May 2023. The risk of bias was assessed using the QUIN tool. Results: Four studies using nanotubes on human sperm were included, nanotubes exposure appears not to affect sperm viability; however, some alterations to motility, velocity and production of reactive oxygen species were reported. Limited evidence is provided because of the small quantity of publications. Conclusions: Nanotubes appear to have no adverse effects on human sperm.